Positions of Social Actors in the Egyptian Revolution: A Micro Level Analysis - İsmail Telci (Akademik İncelemeler Dergisi)
Egyptians witnessed one of the most significant events in the country’s historical development, the so called 25 January Revolution. Anti-government protests started on 25 January 2011 and continued until 11 February of the same year, when President Hosni Mubarak announced his resignation. The revolution has opened the floor for sociologists and other revolution theory scholars as the most novel case in its kind which has similarities to, and differences from all other revolutions that happened in the history. Scholars of revolution emphasize that the most important element of a revolution is its actors. For this very reason, this article analyzes the perceptions, positions and philosophies of major actors of the 25 January Egyptian Revolution immediately before and during the revolution. Specifically, it examines the timing, demands, and claims of major opposition groups and challengers that participated in the revolutionary process. It concludes that almost all anti-Mubarak movements participated in the demonstrations and showed a unified stance against the regime. Regardless of their differences in philosophical orientations and social classes, revolutionary protests included Egyptians from socialists to liberals, seculars to Islamists, Muslims to Christians, who gathered in Tahrir Square and elsewhere, to topple Mubarak regime down. This modest work gives a “descriptive picture” of the persons, groups and organizations who made Egyptian revolution possible.